Analisis Pengendalian Bahaya dengan Metode Swift pada Proses Produksi Calipper Disc Brake di PT. AOP - Muhamad Riyan Iskandar (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
This research discusses the Caliper Disc Brake Production Process at PT. AOP is a company that operates in the manufacturing sector, especially in the process of making front and rear brakes for cars and motorbikes. The problem that occurs in this company is that there is a high potential for work accidents to occur. in the Caliper Disc Brake production process at PT. AOP. Therefore, this research aims to minimize the potential for work accidents and provide suggestions for correct and safe K3 risk control in the manufacture of front and rear brakes for cars and motorbikes. The method used in this research is The Structured What-if Analysis (SWIFT). This method begins by identifying potential hazards, providing an assessment of the level of risk. Based on the results of the research, the results of the risk assessment resulted in a score of 9, namely medium priority/significant risk. There are 4 types of risks involved in making front and rear brakes for cars and motorbikes, namely scratches, tears, pinching, and blisters. Proposed improvements to K3 risks begin with providing warning signs in the use of PPE, creating safe work procedures, monitoring performance evaluations of K3 regulations, providing PPE equipment